Silver and gold nanoparticles from Sargentodoxa cuneata: synthesis, characterization and antileishmanial activity. Issue 90 (2nd October 2015) - Ahmad, Aftab; Syed, Fatima; Shah, Akram; Khan, Zahid; Tahir, Kamran; Khan, Arif Ullah; Yuan, Qipeng
<x xml:space="preserve">Abstract</x> Promising antileishmanial properties were observed with Sargentodoxa cuneata mediated Ag and AuNPs. This study opens a platform for the synthesis of new leishmanicidal agents.